Influence of instruccional strategies based on simulations on the learning level (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2011)
The purpose of this study was to introduce a quantitative experimental instructional strategy based Learning by Simulation, with the intention of evaluating its effect on the learning level of the participating subjects. A single topic on data processing was used in two variants: The first used a traditional method of classroom instruction and the second simulation tools were applied to provide the same instructional content. Participants were assigned to an experimental group or a control group and after application of tests before and after the intervention, the results were subjected to statistical analysis (hypothesis testing). According to the results, it was determined that the multimedia tools did not prove statistically significant in the learning process. Guidelines were raised about the strengths and weaknesses of the strategy in question.
Keywords: university education; meaningful learning; academic performance; simulation systems